Changes in job satisfaction among doctors in Norway from 2010 to 2017: a study based on repeated surveys - Judith Rosta; Olaf G Aasland; Magne Nylenna (BMJ Open)
Objective To assess job satisfaction for different categories of Norwegian doctors from 2010 to 2016–2017.Design Cross-sectional surveys in 2010, 2012, 2014 and 2016–2017 of partly overlapping samples.Setting Norway from 2010 to 2016–2017.Participants Doctors working in different job positions (hospital doctors, general practitioners (GPs), private practice specialists, doctors in academia). Response rates were 67% (1014/1520) in 2010, 71% (1279/1792) in 2012, 75% (1158/1545) in 2014 and 73% (1604/2195) in 2016–2017. The same 548 doctors responded at all four points in time.Main outcome measure Job Satisfaction Scale (JSS), a 10-item widely used instrument, with scores ranging from 1 (low satisfaction) to 7 (high satisfaction) for each item, and an unweighted mean total sum score.Analysis General Linear Modelling, controlling for gender and age, and paired t-tests.Results For all doctors, the mean scores of JSS decreased significantly from 5.52 (95% CI 5.42 to 5.61) in 2010 to 5.30 (5.22 to 5.38) in 2016–2017. The decrease was significant for GPs (5.54, 5.43 to 5.65 vs 5.17, 5.07 to 5.28) and hospital doctors (5.14, 5.07 to 5.21 vs 5.00, 4.94 to 5.06). Private practice specialists were most satisfied, followed by GPs and hospital doctors. The difference between the GPs and the private practice specialists increased over time.Conclusions From 2010 to 2016–2017 job satisfaction for Norwegian doctors decreased, but it was still at a relatively high level. Several healthcare reforms and regulations over the last decade and changes in the professional culture may explain some of the reduced satisfaction.